From Antarctica to cancer research: a novel human DNA topoisomerase 1B inhibitor from Antarctic sponge Dendrilla antarctica - Alessio Ottaviani; Joshua Welsch; Keli Agama; Yves Pommier; Alessandro Desideri; Bill J. Baker; Paola Fiorani (Taylor & Francis Group, 2022)
Nature has been always a great source of possible lead compounds to develop new drugs against several diseases. Here we report the identification of a natural compound, membranoid G, derived from the Antarctic sponge Dendrilla antarctica displaying an in vitro inhibitory activity against human DNA topoisomerase 1B. The experiments indicate that membranoid G, when pre-incubated with the enzyme, strongly and irreversibly inhibits the relaxation of supercoiled DNA. This compound completely inhibits the cleavage step of the enzyme catalytic mechanism by preventing protein binding to the DNA. Membranoid G displays also a cytotoxic effect on tumour cell lines, suggesting its use as a possible lead compound to develop new anticancer drugs.